Analisis Pelaksanaan Program Promosi Dan Mutasi Jabatan Pada Bagian Umum Sekretariat Daerah Kabupaten Raja Ampat - Laut, Fatimah Kapitan; Albab, Ulul (Soetomo Magister Ilmu Administrasi, 2023)
This research aims to determine and explain the operational standards for promotion and transfer procedures, the implementation of promotions, transfers and the factors that make considerations for the implementation of promotions and transfers in the General Section of the Regional Secretariat of Raja Ampat Regency. This research is a type of descriptive research using a survey approach. This research was conducted at the Raja Ampat Regency Regional Secretariat from April to May 2023. The population in this research were all echelon II, III and IV Civil Servants at the Raja Ampat Regency Regional Secretariat, totaling 48 people. For data collection purposes, this was done using questionnaires, interviews and observations. The data analysis technique used is qualitative descriptive analysis. The research results show that (1) the implementation of standard operating procedures (SOP) for promotion and job transfers is carried out in 3 (three) stages, namely the needs identification stage, civil servant talent search. (2) Implementation of promotions and job transfers fulfills the elements of educational qualifications, work performance, discipline, cooperation, work experience/seniority. (3) Factors that are taken into consideration in implementing promotions and job transfers include organizational culture factors, leadership behavior factors, information and communication availability factors, organizational needs factors, political interest factors, professionalism factors, and salary increase factors. Keywords: Program, Promotion, mutation